Pelatihan integrasi permainan tradisional dalam pembelajaran bagi guru sekolah dasar Indonesia Bangkok - Idam Ragil Widianto Atmojo; Matsuri Matsuri; Chumdari Chumdari; Fadhil Purnama Adi; Roy Ardiansyah; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2024)
The Training on Integrating Traditional Games into Learning for Indonesian Elementary School Teachers in Bangkok aims to help teachers recognize and incorporate Indonesian traditional games into their educational curricula. Traditional games, which carry cultural and educational values, are often overlooked in modern education. This training is designed to enable teachers to use games such as congklak, engklek, and rope skipping to enhance students' motor skills, cooperation, and understanding of mathematics and culture. The training method includes theoretical introduction, game demonstrations, and practical workshops, with effectiveness evaluated through questionnaires and group discussions. The results indicate that teachers feel more confident and capable of integrating traditional games into their teaching, while students exhibit increased engagement and motivation. Challenges such as curriculum adjustment and time constraints can be addressed with additional support. This training positively contributes to cultural preservation and provides a more varied learning experience in international schools. Recommendations include developing further training modules and providing ongoing support for greater effectiveness.